Hungarian Monitoring, 7 May 1990 . [Magyar rádiófigyelő], 1990. május 7 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - 4+2 Foreign Ministers meeting - Local government elections in the GDR - New PM will be elected in Riga - Ceauşescu's arms trade scandal Domestic Affairs: - British Royals visit Budapest - The Christian Democrats will lead the Ministry of Health - Miklós Németh meets high ranking clergymen - The remains of Cardinal Mindszenty will be placed in Esztergom until the Pope's visit - New scandal in the Hungarian Social Democratic Party (MSZDP) - Hungarian Red Cross starts anti-poverty campaign - Hungarian Association of the International Children's Safety Service formed Economy: - Recommendation on solving property questions concerning Soviet troops stationed in Hungary - IMF East European aid funds increased - Decision about Hungarian Association of Artisans reforming as an Alliance - László Papócsi is the managing director of Bábolna Agricultural cooperative Külpolitika: - 4+2 külügyminiszteri találkozó - Keletnémet helyhatósági választások - Rigában új kormányfőt választanak - Ceauşescu-féle fegyverszállítási botrány Belpolitika: - Budapestre érkezett a walesi hercegi pár - Keresztény demokraták kaphatják az egészségügyi tárcát - Németh Miklós egyházi vezetőkkel találkozik - Mindszenty bíboros hamvait Esztergomba viszik a pápalátogatásig - Újabb botrány az MSZDP-ben - A Magyar Vöröskereszt akciót indít az országban élő szegénység miatt - Megalakul a Nemzetközi Gyermekmentő Szolgálat magyarországi tagozata Gazdaság: - Javaslat a Magyarországon állomásozó szovjet alakulatok tulajdonviszonyainak elrendezésére - Az IMF növelte a kelet-európai segélyek alapját - Döntés a KIOSZ szövetséggé alakulásáról - Papócsi László a Bábolna igazgatója